Ethnomedicinal and nutritional applications of Rheum maximowiczii Losinsk. in traditional medicine in Uzbekistan - Rakhmataliev, Abdulla; Togaev, Azizbek; Ergashov, Ibrokhimjon; Yusupov, Ziyoviddin (Ethnobotany Research and Applications, 2025)
Background: The aim of this study was to examine the use of Rheum maximowiczii Losinsk. in traditional medicine and to assess its role as a food source. Methods: Information was obtained through fieldwork conducted in natural habitats, a comprehensive review of relevant literature, and ethnobotanical surveys and interviews with local communities and traditional healers. Results: As a result of scientific studies conducted on Rheum maximowiczii, it was found that the root of the plant contains anthraquinone glycosides such as emodin and rhein, while its leaves contain the flavonoid rutin as a bioactive compound. The anthraquinone glycosides were found to enhance intestinal peristalsis and exhibit a laxative effect, whereas rutin demonstrated antioxidant, anti-inflammatory, and capillary-strengthening properties. During the study, it was revealed that in traditional medicine, ointments made from the root of this species are used to treat ailments such as constipation and diarrhea. It was also found that ointments containing this herb are available in pharmacies, and the local population enjoys consuming it in spring. Conclusions: The presence of bioactive compounds in R. maximowiczii indicates its potential as an important source for the development of pharmaceutical products. The consumption of its stems also suggests that it contains low levels of toxic substances and is safe for human health. Therefore, establishing plantations of this plant may prove to be beneficial. Both the stems and roots of the plant can be used to produce valuable food and medicinal products. Keywords: Uzbek traditional medicine, Rheum maximowiczii, red rhubarb, medicinal plant, diseases, rhizome.